Adenosine-5'-Phosphosulfate- and Sulfite Reductases Activities of Sulfate-Reducing Bacteria from Various Environments - Kushkevych, Ivan; Abdulina, Daryna; Kováč, Jozef; Dordević, Dani; Vítězová, Monika; Iutynska, Galyna; Rittmann, Simon K-M R (Biomolecules, 2020)
A comparative study of the kinetic characteristics (specific activity, initial and maximum rate, and affinity for substrates) of key enzymes of assimilatory sulfate reduction (APS reductase and dissimilatory sulfite reductase) in cell-free extracts of sulphate-reducing bacteria (SRB) from various biotopes was performed. The material for the study represented different strains of SRB from various ecotopes. Microbiological (isolation and cultivation), biochemical (free cell extract preparation) and chemical (enzyme activity determination) methods served in defining kinetic characteristics of SRB enzymes. The determined affinity data for substrates (i.e., sulfite) were 10 times higher for SRB strains isolated from environmental (soil) ecotopes than for strains from the human intestine. The maximum rate of APS reductase reached 0.282-0.862 µmol/min×mg-1 of protein that is only 10 to 28% higher than similar initial values. The maximum rate of sulfite reductase for corrosive relevant collection strains and SRB strains isolated from heating systems were increased by 3 to 10 times. A completely different picture was found for the intestinal SRB Vmax in the strains Desulfovibrio piger Vib-7 (0.67 µmol/min × mg-1 protein) and Desulfomicrobium orale Rod-9 (0.45 µmol/min × mg-1 protein). The determinant in the cluster distribution of SRB strains is the activity of the terminal enzyme of dissimilatory sulfate reduction-sulfite reductase, but not APS reductase. The data obtained from the activity of sulfate reduction enzymes indicated the adaptive plasticity of SRB strains that is manifested in the change in enzymatic activity.
Keywords: hydrogen sulfide; cell-free extracts; sulfate-reducing bacteria; sulfan; Biodegradation, Environmental; ecotopes; oxidoreduktasy působící na donory sirných skupin; Adenosine Phosphosulfate; Hydrogen Sulfide; adenosinfosfosulfát; Desulfovibrio desulfuricans; biodegradace; Oxidoreductases Acting on Sulfur Group Donors; Desulfovibrio vulgaris; toxicity